MOF-derived Cu-In2O3 / C composite catalyst as well as preparation method and application thereof
The MOF-derived Cu-In2O3/C composite catalyst catalyzes the co-reduction reaction of carbon dioxide and nitrate under electrochemical conditions, solving the environmental pollution and equipment requirements in the traditional urea synthesis process, and achieving efficient and green urea synthesis.
Patent Information
- Application Number
- CN202510041725.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The existing urea synthesis process has problems such as harsh reaction conditions, environmental pollution and high equipment requirements, making it difficult to achieve green and sustainable urea synthesis.
By preparing MOF-derived Cu-In2O3/C composite catalyst, the co-reduction reaction of carbon dioxide and nitrate is efficiently catalyzed under electrochemical conditions to generate urea by utilizing its highly exposed active sites, optimized surface electronic structure, rapid reaction kinetics and excellent stability.
The efficient synthesis of urea at room temperature and pressure is achieved, and the catalyst exhibits excellent electrocatalytic activity and durability, solving the environmental pollution and equipment requirements in traditional urea synthesis processes.
Smart Images

Figure CN119859822A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a MOF-derived Cu-In2O3 / C composite catalyst. The catalyst can be applied to electrocatalytic co-reduction of nitrate and carbon dioxide to synthesize urea. Background Art
[0002] Urea is not only the most important nitrogen fertilizer in the process of crop growth, but also the key chemical raw material for the production of important chemical products (such as urea-melamine-formaldehyde resin, urea formaldehyde and barbiturates, etc.). At present, industrial synthetic urea is synthesized by liquid ammonia and carbon dioxide under high temperature and high pressure conditions in a two-step process, which has problems such as harsh reaction conditions, environmental pollution and high equipment requirements. Therefore, it is urgent to develop a urea synthesis technology with mild reaction conditions and green and sustainable to replace the traditional two-step urea synthesis process. The greenhouse gas carbon dioxide and nitrogen-containing substances (such as nitrates and nitrites in wastewater) in the environment are co-reduced to urea with higher added value by electrochemical methods, which can not only maximize the utilization of waste resources, but also control water pollution, which is of great significance to the realization of carbon neutrality, the recycling of carbon and nitrogen, the effective storage of intermittent energy and the alleviation of environmental pollution.
[0003] In the electrosynthesis of urea, the design of catalysts is crucial to improve the selectivity and yield of urea. Therefore, to achieve the industrial application of urea electrocatalytic synthesis, it is necessary to develop catalysts with high activity and selectivity. Since it is difficult to achieve the optimal reduction efficiency of two different reaction species (carbon-containing and nitrogen-containing species) by the same metal material at the same time. Therefore, designing bimetallic center catalysts may be an effective way to improve performance through the synergistic effect between different metal catalytic sites.
[0004] Metal-organic framework (MOF) materials have attracted much attention in the field of catalysis due to their highly tunable pore structure and chemical composition. Derivatizing MOF into nanocatalysts not only retains its original high specific surface area and porous structure, but also introduces new active sites. Among various nanostructures, MOF-derived metal / oxide nanomaterials have unique advantages in electrocatalytic applications due to their high conductivity and exposed reaction sites. By introducing suitable metal atoms or oxides into MOF derivatives, the electronic structure of the catalyst can be optimized at the atomic level and its intrinsic activity towards electrochemical reactions can be improved.
[0005] Recent studies have shown that by introducing transition metals (such as copper) into metal oxide catalysts, the adsorption energy of reactants can be optimized, the kinetic barriers of the reaction can be reduced, and the electronic structure (such as the d-band center) can be adjusted, thereby improving the catalytic activity and stability. Indium oxide (In2O3), as a semiconductor material with excellent electrocatalytic properties, can form a pn heterojunction with copper, further improving its electrocatalytic performance.
[0006] By constructing suitable MOF materials as precursors, the Cu-In2O3 / C composite catalyst is derived and prepared. By utilizing its highly exposed active sites, optimized surface electronic structure, fast reaction kinetics and excellent stability, urea can be efficiently synthesized in the co-electroreduction reaction of carbon dioxide and nitrate. Therefore, the development of low-cost, highly active Cu-In2O3 / C composite catalysts is of great research significance for promoting the application of electrochemical synthesis of urea. Summary of the invention
[0007] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a MOF-derived Cu-In2O3 / C composite catalyst, and studies its application in electrocatalytic co-reduction of nitrate and carbon dioxide to synthesize urea.
[0008] The technical solution adopted by the present invention is:
[0009] A MOF-derived Cu-In2O3 / C composite catalyst is prepared by the following method:
[0010] (1) Dissolve 1 mmol of terephthalic acid in 15-30 mL of N,N-dimethylformamide (DMF); then add 0.5-1.5 mmol of indium nitrate tetrahydrate and 0.5-1.5 mmol of sodium nitrate tetrahydrate to the solution.
[0011] mmol of copper nitrate and stirred at room temperature for 1 to 3 hours; then the resulting solution was transferred to a polytetrafluoroethylene-lined autoclave and maintained for solvothermal reaction at 140 to 180°C for 3 to 5 hours; after cooling to room temperature, the resulting precipitate was centrifuged, washed with DMF and deionized water, and then dried in a vacuum oven at 50 to 70°C overnight to obtain a CuIn bimetallic MOF precursor;
[0012] (2) The CuIn bimetallic MOF precursor was placed in a crucible and heated in a tubular furnace under a nitrogen atmosphere at a heating rate of 1 to 3°C / h until it reached 350 to 450°C and maintained for 2 to 4 hours to obtain the final product.
[0013] In the present invention, the selection of reaction conditions has an important influence on the preparation of the catalyst. The typical Cu-In2O3 / C composite catalyst is prepared by a two-step synthesis strategy. In the first step of the solvothermal reaction, the metal salts of copper and indium in the reaction system react with the organic ligand (terephthalic acid) to form a CuIn bimetallic MOF. In the second step, the CuIn bimetallic MOF is annealed to generate a Cu-In2O3 / C composite catalyst.
[0014] A method for preparing a MOF-derived Cu-In2O3 / C composite catalyst, the method comprising the following steps:
[0015] (1) Dissolve 1 mmol of terephthalic acid in 15-30 mL of N,N-dimethylformamide (DMF);
[0016] Subsequently, 0.5-1.5 mmol of indium nitrate tetrahydrate and 0.5-1.5 mmol of copper nitrate were added to the solution and stirred at room temperature for 1-3 hours; the resulting solution was then transferred to a polytetrafluoroethylene-lined autoclave and maintained at 140-180° C. for a solvothermal reaction for 3-5 hours; after cooling to room temperature, the resulting precipitate was centrifuged, washed with DMF and deionized water, and then dried in a vacuum oven at 50-70° C. overnight to obtain a CuIn bimetallic MOF precursor;
[0017] (2) The CuIn bimetallic MOF precursor was placed in a crucible and heated in a tubular furnace under a nitrogen atmosphere at a heating rate of 1 to 3°C / h until it reached 350 to 450°C and maintained for 2 to 4 hours to obtain the final product.
[0018] Furthermore, the morphology, structure and composition of the Cu-In2O3 / C composite catalyst are controlled by controlling the concentrations of indium nitrate tetrahydrate and copper nitrate, the temperature and time of the solvothermal reaction, and the atmosphere and temperature of the annealing.
[0019] The invention discloses an application of a MOF-derived Cu-In2O3 / C composite catalyst, wherein the Cu-In2O3 / C composite catalyst can efficiently catalyze the co-reduction reaction of carbon dioxide and nitrate to generate urea under electrochemical conditions.
[0020] The performance test of electrocatalytic co-reduction of nitrate and carbon dioxide to synthesize urea was carried out at room temperature and pressure. The specific operation process is as follows:
[0021] (1) Weigh 1-3 mg of catalyst sample and disperse it in 0.5-1.5 mL of ultrapure water. Ultrasonicate to obtain a uniform dispersion. Take 1-5 μL of the sample and drop it on the surface of a hydrophobic carbon paper electrode. After drying, drop 1-10 μL of Nafion solution on the catalyst surface to make a working electrode. The carbon rod is used as the counter electrode. An Ag / AgCl electrode is used as a reference electrode in a 0.1 M KNO3 electrolyte.
[0022] (2) When conducting the electrocatalytic co-reduction test of nitrate and carbon dioxide to synthesize urea, a 20 mL / min -1The test was carried out in a 0.1M KNO3 solution of carbon dioxide, and the test procedures of linear sweep voltammetry (LSV) and constant potential method (it) were selected for testing. All potentials in this work need to be converted into E (vs. RHE). The current at different scan rates was observed. Finally, the Faraday efficiency and yield were calculated based on the measured data and the corresponding formula.
[0023] The beneficial effects of the present invention are mainly reflected in:
[0024] (1) A typical Cu-In2O3 / C composite catalyst was successfully prepared by a two-step method, and its application in the electrocatalytic co-reduction of nitrate and carbon dioxide to synthesize urea was demonstrated.
[0025] (2) The Cu-In2O3 / C composite catalyst exhibited excellent electrocatalytic co-reduction of nitrate and carbon dioxide to electrosynthesize urea in the above system, and had outstanding electrocatalytic activity and durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 These are SEM images, TEM images and HRTEM images of the Cu-In2O3 / C composite catalyst at different scales in specific example 1 of the present invention.
[0027] Figure 2 This is the XRD diagram and XPS full spectrum of the Cu-In2O3 / C composite catalyst of specific example 1 of the present invention.
[0028] Figure 3 The cyclic voltammetry curves of the Cu-In2O3 / C composite catalyst at different scan rates of the specific example 1 of the present invention are shown.
[0029] Figure 4 This is the double-layer capacitance curve of the Cu-In2O3 / C composite catalyst of the specific example 1 of the present invention.
[0030] Figure 5 The specific example 1 of the present invention is that the Cu-In2O3 / C composite catalyst is continuously introduced into the reactor for 20 mL min. -1 Linear sweep voltammetry curve of CO2 in 1M KNO3 solution system, Faradaic efficiency of various products at different potentials, yield of urea at different potentials, and Faradaic efficiency and yield at typical potentials for five consecutive cycles.
[0031] Figure 6 The urea yield and Faraday efficiency of the Cu-In2O3 / C composite catalyst at different potentials of the specific embodiment 1 of the present invention are shown.
[0032] Figure 7 This is the SEM image of the Cu-In2O3 / C composite catalyst of specific example 2 of the present invention.
[0033] Figure 8 The cyclic voltammetry curves at different scan rates of the Cu-In2O3 / C composite catalyst of the specific example 2 of the present invention.
[0034] Fig. 9 This is the double-layer capacitance curve of the Cu-In2O3 / C composite catalyst of specific example 2 of the present invention.
[0035] Fig.10 This is the Faradaic efficiency and yield of urea at different potentials of the Cu-In2O3 / C composite catalyst of specific example 2 of the present invention.
[0036] Fig.11 This is the SEM image of the Cu-In2O3 / C composite catalyst of specific example 3 of the present invention.
[0037] Fig.12 The cyclic voltammetry curves of the Cu-In2O3 / C composite catalyst at different scan rates of the specific example 3 of the present invention are shown.
[0038] Fig.13 This is the double-layer capacitance curve of the Cu-In2O3 / C composite catalyst of specific example 3 of the present invention.
[0039] Fig.14 The urea yield and Faraday efficiency of the Cu-In2O3 / C composite catalyst at different potentials of the specific example 3 of the present invention are shown. DETAILED DESCRIPTION
[0040] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:
[0041] Reference Figure 1 to Figure 14 , a MOF-derived Cu-In2O3 / C composite catalyst, prepared by the following method:
[0042] (1) Dissolve 1 mmol of terephthalic acid in 15-30 mL of N,N-dimethylformamide (DMF);
[0043] Subsequently, 0.5-1.5 mmol of indium nitrate tetrahydrate and 0.5-1.5 mmol of copper nitrate are added to the solution, and stirred at room temperature for 1-3 hours; the resulting solution is then transferred to a polytetrafluoroethylene-lined autoclave, and the solvent thermal reaction is maintained at 140-180° C. for 3-5 hours; after cooling to room temperature, the resulting precipitate is centrifuged, washed with DMF and deionized water, and then dried in a vacuum oven at 50-70° C. overnight to obtain CuIn
[0044] Bimetallic MOF precursors;
[0045] (2) The CuIn bimetallic MOF precursor was placed in a crucible and heated in a tubular furnace under a nitrogen atmosphere at a heating rate of 1 to 3°C / h until it reached 350 to 450°C and maintained for 2 to 4 hours to obtain the final product.
[0046] The invention discloses an application of a MOF-derived Cu-In2O3 / C composite catalyst, wherein the Cu-In2O3 / C composite catalyst can efficiently catalyze the co-reduction reaction of carbon dioxide and nitrate to generate urea under electrochemical conditions.
[0047] The performance test of electrocatalytic co-reduction of nitrate and carbon dioxide to synthesize urea was carried out at room temperature and pressure. The specific operation process is as follows:
[0048] 1) Weigh 1-3 mg of catalytic sample and disperse it in 0.5-1.5 mL ultrapure water. Ultrasonicate to obtain a uniform dispersion. Take 1-5 μL of the sample and drop it on the surface of a hydrophobic carbon paper electrode. After drying, drop 1-10 μL of Nafion solution on the catalyst surface to make a working electrode. The carbon rod is used as the counter electrode. An Ag / AgCl electrode is used as a reference electrode in a 0.1 M KNO3 electrolyte.
[0049] 2) When conducting the electrocatalytic co-reduction test of nitrate and carbon dioxide to synthesize urea, a 20 mL / min -1 The test was carried out in a 0.1M KNO3 solution of carbon dioxide, and the test procedures of linear sweep voltammetry (LSV) and constant potential method (it) were selected for testing. All potentials in this work need to be converted into standard hydrogen electrodes. Observe the current under the potential. Finally, the Faraday efficiency and yield are calculated based on the measured data and the corresponding formula.
[0050] Example 1
[0051] A method for preparing a MOF-derived Cu-In2O3 / C composite catalyst, the method comprising the following steps:
[0052] (1) 1 mmol of terephthalic acid was dissolved in 20 mL of N,N-dimethylformamide (DMF); then, 1 mmol of indium nitrate tetrahydrate and 1 mmol of copper nitrate were added to the solution and stirred at room temperature for 2 hours; then, the resulting solution was transferred to a polytetrafluoroethylene-lined autoclave and maintained at 160°C for a solvothermal reaction for 4 hours; after cooling to room temperature, the resulting precipitate was centrifuged, washed with DMF and deionized water, and then dried in a vacuum oven at 60°C overnight to obtain a CuIn bimetallic MOF precursor;
[0053] (2) The CuIn bimetallic MOF precursor was placed in a crucible and heated in a tube furnace under a nitrogen atmosphere at a heating rate of 2 °C / h until it reached 400 °C and maintained for 3 h to obtain the final product.
[0054] The scanning electron microscope image, transmission electron microscope image and high-resolution transmission electron microscope image of the Cu-In2O3 / C composite catalyst obtained in Example 1 are shown in FIG. Figure 1 The XRD pattern of the Cu-In2O3 / C composite catalyst obtained in Example 1 is shown in Figure 2 The cyclic voltammetry curves of the Cu-In2O3 / C composite catalyst at different scan rates obtained in the specific example 1 are shown in FIG. Figure 3 The double layer capacitance curve of the Cu-In2O3 / C composite catalyst in the specific embodiment 1 is shown in FIG. Figure 4 The Cu-In2O3 / C composite catalyst in Example 1 was continuously introduced for 20 mL min. -1 The linear sweep voltammetric curves of CO2 in 1M KNO3 solution system, the Faraday efficiency of various products at different potentials, the yield of urea at different potentials, and the Faraday efficiency and yield at typical potentials under five consecutive cycles are shown in Figure 2. Figure 5 The urea Faraday efficiency and yield of the Cu-In2O3 / C composite catalyst obtained in Example 1 at different potentials are shown in Table 1. Figure 6 .
[0055] First, the morphology and structure of the prepared Cu-In2O3 / C composite catalyst were characterized by scanning and transmission electron microscopy. The scanning electron microscope image proved that the sample was a composite material composed of a large number of nanoparticles loaded on a rod-shaped carbon-based material. From the transmission electron microscope image, the Cu-In2O3 heterogeneous nanoparticles loaded on the rod-shaped carbon-based material were more clearly observed. The high-resolution transmission electron microscope image showed that the carbon-loaded Cu-In2O3 heterogeneous nanoparticles were highly crystalline. Through the XRD spectrum, obvious peaks of copper and indium oxide were observed, indicating that copper and indium oxide were successfully converted from MOF precursors to form Cu-In2O3 heterogeneous nanostructures. The XPS spectrum further confirmed the presence of copper, indium and carbon elements. Next, the electrocatalytic co-reduction of carbon dioxide and nitrate for electrosynthesis of urea by the Cu-In2O3 / C catalyst was explored. First, the electrochemical active area of the catalyst was calculated by the double-layer capacitance curve. Compared with other Cu-In2O3 catalyst samples with different copper / indium ratios, the typical Cu-In2O3 / C has a higher catalytic active area, indicating that the catalyst with this copper / indium ratio can provide more electrochemical active sites after heterojunction formation and electronic regulation. -1In the 0.1 M potassium nitrate electrolyte containing carbon dioxide, the Faradaic efficiency of urea can reach 31.29% at a potential of -0.5 V, and the urea yield can reach 3779.27 μg h -1 mg -1 Compared with other catalysts, the typical samples have better electro-synthesized urea activity and efficiency. The typical Cu-In2O3 / C was tested for cyclic stability. After 5 consecutive cycles, its urea Faraday efficiency and urea yield showed almost no attenuation, indicating that it has excellent electro-synthesized urea stability.
[0056] Example 2
[0057] A method for preparing a MOF-derived Cu-In2O3 / C composite catalyst, the method comprising the following steps:
[0058] (1) 1 mmol of terephthalic acid was dissolved in 15 mL of N,N-dimethylformamide (DMF). Subsequently, 0.5 mmol of indium nitrate tetrahydrate and 1.5 mmol of copper nitrate were added to the solution and stirred at room temperature for 1 hour; the resulting solution was then transferred to a polytetrafluoroethylene-lined autoclave and maintained at 140°C for a solvothermal reaction for 3 hours; after cooling to room temperature, the resulting precipitate was centrifuged, washed with DMF and deionized water, and then dried in a vacuum oven at 50°C overnight to obtain a CuIn bimetallic MOF precursor;
[0059] (2) CuIn-MOF was placed in a crucible and heated in a tube furnace under a nitrogen atmosphere at a heating rate of 1 °C / h until it reached 350 °C and maintained for 2 h to obtain the final product.
[0060] The scanning electron microscope image of the Cu-In2O3 / C composite catalyst obtained in this example is as follows Figure 7 As shown in the figure, it can be seen that the carbon-based material loads nanoparticles in a rod-like shape. The double-layer capacitance was determined by cyclic voltammetry to be 1.15 mF cm -2 ( Figure 8 and Fig. 9 ). Continue to flow 20mL min -1 The performance of electrosynthesized urea was tested in 1M KNO3 solution containing CO2. Fig.10 As shown in Figure 2, the Faradaic efficiency of the best urea synthesis at -0.5 V is 27.43%, and the corresponding urea yield is 2884.24 μgh. -1 mg -1 .
[0061] Example 3
[0062] A method for preparing a MOF-derived Cu-In2O3 / C composite catalyst, the method comprising the following steps:
[0063] (1) Dissolve 1 mmol of terephthalic acid in 30 mL of dimethylformamide (DMF).
[0064] Subsequently, 1.5 mmol of indium nitrate tetrahydrate and 0.5 mmol of copper nitrate were added to the solution, which was then stirred at room temperature for 3 hours. The resulting solution was then transferred to a polytetrafluoroethylene-lined autoclave and kept at 180 ° C for 5 hours. After cooling to room temperature, a precipitate was obtained. The precipitate was centrifuged, washed with DMF and deionized water, and then dried in a vacuum oven at 70 ° C overnight to obtain CuIn-MOF;
[0065] (2) CuIn-MOF was placed in a crucible and heated in a tube furnace under a nitrogen atmosphere at a heating rate of 3 °C / h until it reached 450 °C and maintained for 4 h to obtain the final product.
[0066] The scanning electron microscope image of the Cu-In2O3 / C composite catalyst obtained in this example is as follows Fig.11 As shown in Figure 2, the morphology of the catalyst is a nanorod-like morphology composed of carbon-based materials and nanoparticles. The double-layer capacitance of the catalyst measured by cyclic voltammetry is 1.47 mF cm -2 ( Fig.12 and Fig.13 ). Continue to flow 20mL min -1 The performance of electrosynthesized urea was tested in 1M KNO3 solution containing CO2. Fig.14 As shown in Figure 2, the Faradaic efficiency of the best urea synthesis at -0.5 V was 29%, and the corresponding urea yield was 2848.85 μg h -1 mg -1 .
[0067] The contents described in the embodiments of this specification are merely an enumeration of the implementation forms of the inventive concept and are for illustrative purposes only. The protection scope of the present invention should not be considered to be limited to the specific forms described in this embodiment, and the protection scope of the present invention also extends to equivalent technical means that can be thought of by ordinary technicians in this field based on the inventive concept.
Claims
1. A MOF-derived Cu-In2O3 / C composite catalyst, characterized in that: Prepared by the following method: (1) 1 mmol of terephthalic acid is dissolved in 15-30 mL of N,N-dimethylformamide (DMF); then, 0.5-1.5 mmol of indium nitrate tetrahydrate and 0.5-1.5 mmol of copper nitrate are added to the solution and stirred at room temperature for 1-3 hours; then, the resulting solution is transferred to a polytetrafluoroethylene-lined autoclave and maintained at 140-180°C for a solvothermal reaction for 3-5 hours; after cooling to room temperature, the resulting precipitate is centrifuged, washed with DMF and deionized water, and then dried in a vacuum oven at 50-70°C overnight to obtain a CuIn bimetallic MOF precursor; (2) The CuIn bimetallic MOF precursor was placed in a crucible and heated in a tubular furnace under a nitrogen atmosphere at a heating rate of 1 to 3°C / h until it reached 350 to 450°C and maintained for 2 to 4 hours to obtain the final product.
2. A method for preparing the MOF-derived Cu-In2O3 / C composite catalyst as claimed in claim 1, characterized in that: The method comprises the following steps: (1) 1 mmol of terephthalic acid is dissolved in 15-30 mL of N,N-dimethylformamide (DMF); then, 0.5-1.5 mmol of indium nitrate tetrahydrate and 0.5-1.5 mmol of copper nitrate are added to the solution and stirred at room temperature for 1-3 hours; then, the resulting solution is transferred to a polytetrafluoroethylene-lined autoclave and maintained at 140-180°C for a solvothermal reaction for 3-5 hours; after cooling to room temperature, the resulting precipitate is centrifuged, washed with DMF and deionized water, and then dried in a vacuum oven at 50-70°C overnight to obtain a CuIn bimetallic MOF precursor; (2) The CuIn bimetallic MOF precursor was placed in a crucible and heated in a tubular furnace under a nitrogen atmosphere at a heating rate of 1 to 3°C / h until it reached 350 to 450°C and maintained for 2 to 4 hours to obtain the final product.
3. The preparation method according to claim 2, characterized in that: The morphology, structure and composition of the Cu-In2O3 / C composite catalyst can be controlled by controlling the concentrations of indium nitrate tetrahydrate and copper nitrate, the temperature and time of the solvothermal reaction, and the atmosphere and temperature of the annealing.
4. An application of the MOF-derived Cu-In2O3 / C composite catalyst as claimed in claim 1, wherein the Cu-In2O3 / C composite catalyst can efficiently catalyze the co-reduction reaction of carbon dioxide and nitrate to produce urea under electrochemical conditions.
Citation Information
Patent Citations
Preparation method using heteronuclear MOFs template to prepare metal doped indium oxide photocatalyst
CN109821526A
Carbon dioxide electrochemical reduction copper-indium bi-metal co-doped organic frame catalyst, as well as preparation method and application thereof
CN110756193A
Indium oxide loaded copper single atom tandem type photocatalyst as well as preparation and application thereof
CN116651459A
Preparation method and application of copper-indium bimetallic oxide cage electro-catalytic material
CN117488343A
Preparation and use of high-stability catalyst for co 2 hydrogenation to ethanol
WO2024230343A1
Cited By
Preparation method of supported catalyst for hydrogen production by methanol steam reforming
CN120132890A
Preparation method of supported hydrogen production catalyst for methanol steam reforming
CN120132890B